Fabrication of silicon microwires by a combination of chemical etching steps and their analysis as anode material in Li-ion batteries. (10th November 2019) - Pérez-Díaz, Oscar; Quiroga-González, Enrique; Hansen, Sandra; Silva-González, Nicolás Rutilo; Carstensen, Jürgen; Adelung, Rainer
ABSTRACT: This work presents a thorough study of Si microwires obtained by a novel combination of chemical etching steps, for their application as anode material in Li-ion batteries. The fabrication process starts with standard photolithography followed by a metal-assisted chemical etching step and anisotropic etching. This process can be performed in any chemical laboratory. The final structures possess a diameter and a length of 1.5 and 24 µm, respectively. Paste electrodes were prepared using the Si microwires and were tested in half-battery cells. Cyclic voltammetry and impedance spectroscopy evidenced the formation of Li–Si alloys and a solid electrolyte interface. The lithiated wires are mechanically stable upon lithiation, even when they expand to the 256% of their original volume.